2016
DOI: 10.1242/bio.017194
|View full text |Cite
|
Sign up to set email alerts
|

AβPP processing results in greater toxicity per amount of Aβ1-42 than individually expressed and secreted Aβ1-42 inDrosophila melanogaster

Abstract: The aggregation of the amyloid-β (Aβ) peptide into fibrillar deposits has long been considered the key neuropathological hallmark of Alzheimer's disease (AD). Aβ peptides are generated from proteolytic processing of the transmembrane Aβ precursor protein (AβPP) via sequential proteolysis through the β-secretase activity of β-site AβPP-cleaving enzyme (BACE1) and by the intramembranous enzyme γ-secretase. For over a decade, Drosophila melanogaster has been used as a model organism to study AD, and two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…A). Flies were analysed at day 21, a time point corresponding to the median survival time previously observed for AβPP‐BACE1 flies . The majority of all TUNEL‐positive cells were observed in the medulla and the lamina (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…A). Flies were analysed at day 21, a time point corresponding to the median survival time previously observed for AβPP‐BACE1 flies . The majority of all TUNEL‐positive cells were observed in the medulla and the lamina (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In our previous study, longevity and locomotor analyses showed significant toxic effects for both the Aβ42 flies and AβPP‐BACE1 flies . The time frame selected for this study was 21 days, corresponding to the median survival time for the AβPP‐BACE1 flies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations